2020
DOI: 10.1021/acs.jproteome.0c00622
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal and Early Postnatal Cerebral d-Aspartate Depletion Influences l-Amino Acid Pathways, Bioenergetic processes, and Developmental Brain Metabolism

Abstract: D-Amino acids were believed to occur only in bacteria and invertebrates. Today, it is well known that D-amino acids are also present in mammalian tissues in a considerable amount. In particular, high levels of free D-serine (D-Ser) and Daspartate (D-Asp) are found in the brain. While the functions of D-Ser are well known, many questions remain unanswered regarding the role of D-Asp in the central nervous system. D-Asp is very abundant at the embryonic stage, while it strongly decreases after birth because of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…Increased aspartate and glutamate levels were detected in the hippocampi of seven-week-old rats experiencing sleep fragmentation stress relative to controls [ 60 ]. Moreover, a metabolome study of the whole brain in mice concluded that aspartate deficiency influences alanine, valine, glutamate, threonine, and glycine amino acid pathways [ 61 ]. The aspartate profile was correlated with metabolites that participate in brain development and function, including choline and creatine, and in brain energy metabolism, including glucose and lactate.…”
Section: Discussionmentioning
confidence: 99%
“…Increased aspartate and glutamate levels were detected in the hippocampi of seven-week-old rats experiencing sleep fragmentation stress relative to controls [ 60 ]. Moreover, a metabolome study of the whole brain in mice concluded that aspartate deficiency influences alanine, valine, glutamate, threonine, and glycine amino acid pathways [ 61 ]. The aspartate profile was correlated with metabolites that participate in brain development and function, including choline and creatine, and in brain energy metabolism, including glucose and lactate.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative analysis of NMR spectra was performed using NMRProcFlow 1.4.14 (INRA UMR 1332 BFP, Bordeaux Metabolomics Facility, Villenave d’Ornon, France) ( Jacob et al., 2017 ) following the method reported by Grimaldi et al. ( Grimaldi et al., 2021 ). Briefly, corrections of phasing and baseline were performed manually for all spectra using TOPSPIN version 3.2.…”
Section: Methodsmentioning
confidence: 99%
“…NMR data were acquired on a Bruker. NMR spectra analysis and metabolite quantification were then performed by using the online server NMRProcFlow (INRA UMR 1332 BFP, Bordeaux Metabolomics Facility, Villenave d'Ornon, France) [116] following the method reported by Grimaldi et al [117]. Briefly, corrections of phasing and baseline were performed manually for all spectra using TOPSPIN version 3.2.…”
Section: Nmr Data Analysismentioning
confidence: 99%